1985
DOI: 10.1159/000180068
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Growth Hormone Response to Synthetic GH-RH<sub>1-4</sub><sub>4</sub> in 52 Children and Adults with Growth Hormone Deficiency of Various Etiologies

Abstract: 52 patients (42 children and 10 adults) with growth hormone deficiency (GHD), grouped into four diagnostic categories, and 6 children with constitutional short stature who served as controls were tested for plasma GH response to synthetic GH-RH1–44 given in an intravenous bolus. The response was classified into three degrees according to the magnitude of the maximal rise: Good, > 9 ng/ml; Partial, 3.1–9.0 ng/ml; None, ≤ 3 ng/ml. Among the GHD patients the highest response was observed in patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1986
1986
2002
2002

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 11 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…Synthetic GRHi_44 has been found to be useful in clinical practice for the evaluation of pituitary somatotroph function Rosen¬ thal et al 1983;Wood et al 1983;Pertzelan et al 1985). There is, however, only one report dealing with the response of hGH to GRH in obese individuals and in this series the subjects were adults with morbid obesity (Williams et al 1984).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Synthetic GRHi_44 has been found to be useful in clinical practice for the evaluation of pituitary somatotroph function Rosen¬ thal et al 1983;Wood et al 1983;Pertzelan et al 1985). There is, however, only one report dealing with the response of hGH to GRH in obese individuals and in this series the subjects were adults with morbid obesity (Williams et al 1984).…”
Section: Discussionmentioning
confidence: 86%
“…Our investigation of 14 obese juveniles revealed two patterns of plasma hGH response to GRH. In the group with so-called simple obesity-the re¬ sponse of hGH to GRH was good (11.8 + 2.4 ng/ml) but less than in normal adolescents (49 ± 34; range 19-90 ng/ml) (Pertzelan et al 1985), whereas in the group suffering from syndromes associated with obesity it was very low (3.2 ± 1.4 ng/ml). Williams et al (1984) reported that the hGH response to GRH was related to the degree of obesity.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…It is difficult to compare reported data because the doses of GHRH administered have varied [3, 4], as have the limit of GH peak defining the low response, and the association of GHRH with other stimuli [1, 5]. The factors influencing the response are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Gestational age correlated positively with both basal and peak growth hormone concentra tions in our patients. In conclusion, first, neonates studied in their first days of life have high basal levels of growth hormone and fail to further secrete any significant amount of growth hormone following a single dose of GHRH, and, second, premature newborns secrete signif icantly less growth hormone than do term neonates.The availability of human pancreatic tu mor growth hormone-releasing hormones (hpGHRH-40 and hpGHRH-44), the latter of which is almost certainly identical to hy pothalamic GHRH, has allowed a number of investigators to study growth hormone re lease in normal adults [1][2][3], adolescents and older children [4,5] and in a diverse group of children with short stature [2][3][4][5].Adults and children undergoing pubertal changes differ in their response to GHRH; in adults it may be less brisk than in children [3] and the response may in fact decrease with advancing age [7], but there is a marked rise in GHRH levels during puberty [4,5],The growth hormone response to GHRH has to our knowledge only been evaluated in newborns in one previous study [6] and these …”
mentioning
confidence: 99%